Desarrollo de un sistema de visualización y análisis de datos de un Refrigerador Doméstico utilizando MATLAB y la plataforma ThingSpeak Internet de las Cosas (IoT). (2021)
The power consumption of domestic refrigerators shown by manufacturers is the result of a set of internationally standardized measurements. The tests performed to determine it are highly expensive due to the conditions that need to be established in laboratories. Several investigations carried out in real working conditions are limited, and their main problem has to do with obtaining the behavior of the variables under these conditions. This document presents a proposal for a system of measurement and display of data from a domestic refrigerator to analyze the behavior of energy consumption and thermodynamic parameters (temperature, pressure, power and COP) in real operating conditions, case study Neiva (Huila). The virtual instrumentation used to simulate the variables is supported by an Arduino programming module and is integrated to the IoT ThingSpeak platform. With this solution it was possible to establish different correlations between some of the variables measured by means of MatLab. To carry out this theoretical research, the historical logical method was used for the study of the art, the method of induction deduction to determine the regularities of the hermetic compressors, the analysis and synthesis to determine the key factors that influence the phenomenon. Finally, it was found that the power consumption of the domestic refrigerator in real operating conditions for tropical climates (above 32°C ambient temperature) and voltage variations [ 97 (V)-127 (V)] can be up to 30% higher than that provided by the manufacturer, since these variables greatly affect the cooling power and COP variables, which are extremely important in consumption.